2006
DOI: 10.1097/01.ogx.0000201912.28603.d2
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Risk Estimation of Placental Abruption

Abstract: Short title: Risk estimation of placental abruption 2 CONDENSATION Prior second trimester, third trimester, and repeated fetal loss may be used to predict increased risk of placental abruption. Lindqvist PG ABSTRACTObjective: Several variables related to increased risk of placental abruption are also risk factors for venous thromboembolism. Prior second trimester-, third trimester, and repeated fetal loss are reported to be associated to thrombophilias. However, it is yet not known if they are also related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…There is some evidence that placental abruption occurs in families (47)(48)(49). According to one study, placental abruption appears to cluster in families of an index patient with recurrent placental abruption (47). According to another study, 5% of women with abruption reported first degree relatives with abruption (48).…”
Section: Prediction Of Placental Abruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some evidence that placental abruption occurs in families (47)(48)(49). According to one study, placental abruption appears to cluster in families of an index patient with recurrent placental abruption (47). According to another study, 5% of women with abruption reported first degree relatives with abruption (48).…”
Section: Prediction Of Placental Abruptionmentioning
confidence: 99%
“…Risk factor analysis. Risk score analyses and mathematical modeling have been developed in order to predict placental abruption (47,78). An analysis of 52 obstetric risk factors related to placental abruption was used to create a mathematical model (78).…”
Section: Prediction Of Placental Abruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] . Recently placental abruption has been reported to be more prevalent in patients with thrombophilia and in women with family history of venous thromboembolism [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Placental abruption refers to the separation of a normally sited placenta from the uterine wall after 20 weeks of gestation and prior to birth [1]. Abruption is the most common cause of late pregnancy bleeding [2], and is associated with significant perinatal mortality and morbidity [3].…”
Section: Introductionmentioning
confidence: 99%